The Cenozoic spatiotemporal exhumation of the SE Tibetan Plateau: insight from the data mining and modeling of low-temperature thermochronology - Liu, Fangbin; Wang, Min; Liu, Honghua; Ni, Ran (Frontiers in Earth Science, 2023)
The SE Tibetan Plateau is distinct from other margins due to its high elevation, long wavelength, and low relief. A clear understanding of the Cenozoic exhumation history of this region is key to understanding the special geomorphological process and the associated mechanisms. Previous thermochronological studies have either focused on vertical sections or on horizontal variations in the local regions. However, the spatiotemporal exhumation pattern of the entire SE Tibetan Plateau is enigmatic. In this article, we have compiled 1,202 thermochronological data using joint Kernel density estimation and linear inversion approaches to address the exhumation process. The results reveal that at least six episodes of rapid cooling have occurred since the Cenozoic, of ~61-58 Ma, 38-35 Ma, 32-23 Ma, 18-13 Ma, 11-6 Ma, and 4-3 Ma, respectively. Furthermore, the entire SE Tibetan Plateau underwent spatially inhomogeneous exhumation throughout the main episodes. We infer that all cooling episodes may be attributed to the lateral extrusion and continuous convergence between the Indian and Eurasian continents. Meanwhile, climate changes (e.g., intensified Asian summer monsoon, and glacial processes) have also played a non-negligible role in shaping the landscape since the Miocene. Our results will provide new insights into geodynamic mechanisms of the exhumation processes throughout the whole SE Tibetan Plateau since the Cenozoic.